Binding patterns of IgE antibodies in sera of rubber tappers to fresh Hevea latex serum proteins - Hasma H; Azizah Yip M; Mok K L; Nasuruddin B A; Shahnaz M (Journal of Rubber Research, 1998)
The binding patterns of IgE antibodies to fresh natural rubber latex B- and C- serum proteins were determined by sodium dodecyl sulphate-polyacrylamide gel electrophoresis immunoblotting technique. All the IgE samples were from Malaysian rubber tappers who had been skin-prick tested with extracts of gloves and food: avocado, potato, tomato and watermelon. Two of the five IgE samples from tappers reacting to gloves bound to latex proteins, specifically to 35, 38 and 40 kD B-serum proteins and to 30 kD and 75 kD. The heterogeneous binding pattern was also demonstrated by eleven of the twenty IgE serum samples of tappers reacting to food and by twenty-five of the hundred and thirty-six serum samples of tappers reacting negatively to both gloves and food. The fact that only two of the thirty-eight serum samples that showed strong multiple binding pattern coresponded to a positive skin-prick test to gloves, indicated that in vitro immunoblotting using IgE antibodies in human blood is an unreliable indicator of latex allergy.